Case Studies in Superconducting Magnets Design and Operational Issues - Iwasa, Yukikazu. (Selected Topics in Superconductivity, 1994)
Designed for graduate students in mechanical engineering, this textbook discusses the basic concepts of superconducting magnet technology. Important topics covered include field distribution, magnets, force, thermal stability, dissipation, and protection. To help the students excel in the field, each chapter contains tutorial problems, accompanied by solutions, utilizing solenoidal magnets as examples.